Právní režim Antarktidy, zejména ochrana jejího životního prostředí a postavení České republiky - Gerhardová, Ivana (Univerzita Karlova, Právnická fakulta, 2012)
The Legal regime of Antarctica, primarily the protection of its environment and the position of the Czech Republic The purpose of my thesis is to analyse a legal regime of Antarctica, with regards to protection of its environment and position of the Czech Republic. The thesis is divided into four chapters. Chapter One contains basic introduction of the Antarctic Continent, its geography and history. Chapter Two investigates legal regime constituted in Antarctica by the Antarctic Treaty and other international documents, known as the Antarctic Treaty System. This chapter consists of six parts, each concentrating on special subject. Part one examines the path of development the Antarctic treaty, part two deals with treaty itself, part three looks at dispute settlement, part four focuses on liability in this international space, part five addresses the issue of inspections held in Antarctica. Part six describes structure and organisation of the Antarctic Treaty System, Antartic Treaty Consultative Meetings, its legal documents and Secretariat of the Antarctic Treaty. Chapter Three concentrates on the problem of protection of antarctic environment. Firts part of this chapter focuses on protection of living resources, guaranteed by the Convention for the Conservation of Antarctic Seals and the. Shrnutí Cílem této práce je prozkoumat právní režim panující v Antarktidě, se zaměřením na mezinárodní instrumenty chránící její životního prostředí a pozici České republiky. Práce je rozdělena do čtyř základních částí. V první části se zabývám stručným exkurzem do historie a přírodních podmínek panujících v Antarktidě. Ve druhé části se zaměřuji na samostatný právní režim, zvaný Antarktický smluvní systém (ATS), sestávající se ze Smlouvy o Antarktidě, Úmluvy o zachování antarktických tuleňů, Úmluvy o zachování antarktických mořských živých zdrojů, Protokolu o ochraně životního prostředí ke Smlouvě o Antarktidě (Madridský Protokol) a dalších instrumentů, přijímaných na jejich základě. Jednotlivé kapitoly této části jsem ...